SOSIALISASI DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA YAYASAN AL-MUNASHARAH - Yusuf, Yusuf; Fitri, Euis Nessia; Rahmawati, Titah (Asosiasi Dosen Muda Indonesia, 2024)
The Socialization and Training on Financial Statement Preparation program was conducted from November 11 to December 5, 2024, at Yayasan Al Munasharah, Pondok Cabe Ilir. This program aimed to enhance the understanding and skills of the foundation's management in preparing financial statements based on the Financial Accounting Standards (SAK). Through lectures, discussions, and simulations, participants gained knowledge on transaction recording, and the preparation of balance sheets, income statements, and cash flow statements. Evaluations showed a significant improvement in participants' understanding, positively impacting the transparency and accountability of the foundation's financial governance. This program serves as a strategic model to support the sustainability of educational foundation operations.